Policy and practice in European human resource management : the price Waterhouse Cranfield survey - Brewster, Chris; Hegewisch, Ariane (Routledge, 1994)
Human resource management in Europe: issues and opportunities. The integration of human resource management and corporate strategy. The education and training of human resource managers in Europe. Human resource and line management...